Spider silk: from super strong webs to customisable synthetic protein - Smith, Charlotte Rose (2022)
Spider silks display a remarkable array of properties, making them an area of great interest in biotechnological research. Silk has many of the desired properties needed for a biomaterial; it is flexible, biocompatible and can have remarkable tensile strength, which makes it as strong and tough as some man-made materials such as Kevlar and steel. This combination of physical properties and biocompatibility makes it an especially interesting candidate for both bioengineering and medical applications. Due to this, and the relative difficulty of farming spiders due to their cannibalistic nature, much interest has focussed on the recombinant production of synthetic spider silk.